2014
DOI: 10.4028/www.scientific.net/amm.513-517.2843
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Load Simulation and Structure Improvement of High Speed Diesel Engine Piston

Abstract: In order to solve cylinder-scraping of a four-cylinder high speed diesel engine, based on the measurement of piston temperature, the piston temperature field was numerically simulated by using temperature fitting method, the calculation results were well consistent with the measured temperature. By finite element analysis of piston thermal load based on the calculation results as temperature load, enlarging oil cooling cavity in the piston head was proposed to enhance cooling locally, which could effectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Liu et al 19 combined the first-order optimization algorithm with finite element software to analyze and optimize the piston, which eliminating the problem of sizeable local temperature differences caused by piston structure factors. Ning et al 20,21 studied the engine cylinder pulling phenomenon and accurately calculated the piston temperature field using the temperature fitting method. It is concluded that the engine cylinder pulling phenomenon is mainly resulted from the radial deformation of the piston head and skirt and excessive heat load.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 19 combined the first-order optimization algorithm with finite element software to analyze and optimize the piston, which eliminating the problem of sizeable local temperature differences caused by piston structure factors. Ning et al 20,21 studied the engine cylinder pulling phenomenon and accurately calculated the piston temperature field using the temperature fitting method. It is concluded that the engine cylinder pulling phenomenon is mainly resulted from the radial deformation of the piston head and skirt and excessive heat load.…”
Section: Introductionmentioning
confidence: 99%